2009
DOI: 10.1007/s00127-009-0500-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of workers in Toulouse 2 years after the industrial AZF disaster: first results of a longitudinal follow-up of 3,000 people

Abstract: This study shows links between the industrial disaster and psychological distress 2 years afterwards. The results about risk factors differ according to sex, and identify particularly vulnerable populations. It should guide preventive interventions in such situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
1
25
1
1
Order By: Relevance
“…As it is not possible to compare respondents and non-respondents, we cannot say whether there was a selection bias, although this is very probable. In the context of empathy and social desirability after the disaster, it is probable that the initial state of health (injuries), or its perception, may be selection factors [14]. Furthermore, a recent work has shown that participation in trauma-focused epidemiological studies may result in sensitization to health problems [44].…”
Section: Discussionmentioning
confidence: 99%
“…As it is not possible to compare respondents and non-respondents, we cannot say whether there was a selection bias, although this is very probable. In the context of empathy and social desirability after the disaster, it is probable that the initial state of health (injuries), or its perception, may be selection factors [14]. Furthermore, a recent work has shown that participation in trauma-focused epidemiological studies may result in sensitization to health problems [44].…”
Section: Discussionmentioning
confidence: 99%
“…This cohort comprised 1,333 men and 1,514 women, of whom 29.7% of men and 24.9% of women were less than 1.7 kilometers (km) from the explosion. Compared with the whole pool of the cross‐sectional study from which the cohort was mainly derived, the cohort members were older and included more blue‐collar workers and intermediate occupations (foreman, technician; Cohidon et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…There were 31 deaths (including 21 workers) initially reported, with more than 3,000 people injured and more than 1,300 companies affected to varying degrees (Diène et al., ). In the days following the explosion, a plan for the epidemiological follow‐up of its health consequences was set up, which included a section related to workers (Cohidon et al., ; Diène et al., ). A cross‐sectional survey and then a cohort follow‐up were planned to describe over a 5‐year period the trends in their health, and social and occupational status in relation to the explosion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies based on the 2004 tsunami in Southeast Asia clearly distinguished direct from indirect exposure. [44][45][46][47][48] Key Features of the Present Study Results of this study provide a detailed account of the pervasiveness and potency of the psychological effects of indirect exposure to disaster. 25 A study of refugees from Sri Lanka and Indonesia who had been ''living in exile'' in Norway prior to the disaster found that psychological symptom levels were associated with the degree of indirect exposure to the tsunami and chronic stressors of refugee life.…”
Section: Indirect Earthquake Exposure Measures In Relation To Trauma-mentioning
confidence: 99%